A Study of natural radioactivity in urban parks - Gelatsoras, Foivos Panagiotis; Mertzimekis, Theo; Krassakis, Pavlos; Lagaki, Varvara; Madesis, Ioannis; Siltzovalis, Georgios (HNPS Advances in Nuclear Physics, 2024)
Urban parks are typically undisturbed natural locations inside metropolitan areas, attracting human recreation activities. The present work focuses on studying the radioactivity levels in urban parks in the metropolitan areas of Athens, Barcelona, and Bucharest to establish a baseline of the overall environmental load and the associated contribution to background radiation dose levels. A total of 25 soil samples were collected, prepared, and measured with high-resolution gamma spectroscopy at the Environmental Radioactivity Laboratory of NKUA. Specific activities for naturally occurring isotopes (40K, U-, and Th-series) and anthropogenic radiocesium have been deduced. The results are correlated to the level of human intervention in the parks but also show that traces of 137Cs from the Chernobyl fallout are still present in the most undisturbed soils, reaching values up to 86±4 Bq/kg. All the data has been used to populate a GIS-based informational database featuring various layers of storyboards and metadata.